Contribution to the knowledge of the weevil subgenus Arammichnus Gozis, genus Otiorhynchus Germar (Coleoptera, Curculionidae) from Sicily and the Sicilian islands - Baviera, Cosimo; Magnano, Luigi (Zootaxa, 2010)
New data are presented on the taxonomy and distribution of some species of Otiorhynchus Germar, subgenus Arammichnus Gozis, in Sicily. Otiorhynchus (Arammichnus) ferrarii Miller is recorded from Sicily for the first time. Three new species are described: Otiorhynchus (Arammichnus) vagans n. sp., Otiorhynchus (Arammichnus) pseudosetosulus n. sp., and Otiorhynchus (Arammichnus) adrianus n. sp. The number of known Otiorhynchus (Arammichnus) species thereby rises to 66; 25 of which are present in Sicily and the lesser Sicilian islands.